Numeryczne rozwiązanie równań termosprężystości - BORKOWSKI, Szczepan (Engineering Transactions, 1970)
Numerical solution of the equations of thermoelasticityIn this paper is given the matrix representation for initial boundary problems of the dynamic equations of conjugated thermoelasticity. Subsequently, the matrix representations are derived for particular cases of these equations (conjugated and non-conjugated quasi-static problems). Finally, to the initial-boundary problems so conceived is applied the method of finite differences, proving that it can be described by a single matrix equation. In this equation, the unknown quantities are the values of the functions of displacements and temperature at determined points of the discrete set of space-time.